Studying early Islam in the third millennium: a bibliometric analysis - Halil İbrahim Yılmaz; Mahmut Cihat İzgi; Enes Ensar Erbay; Samet Şenel (Humanities & Social Sciences Communications)
Abstract Early Islam, spanning its nascent centuries from the early 7th century, encompasses a pivotal epoch covering the life and teachings of the Prophet Muhammad, the establishment of Islamic principles, the codification of the Qur’ān, and the evolution of Islamic law and theological thought. This article outlines the findings of a pioneering bibliometric analysis of 764 high-value articles on early Islam from the Web of Science (WoS) database and unveils critical trends. This study, which notably highlights increased academic activities, particularly interdisciplinary expansion into archaeology and related fields, demonstrates a contemporary upsurge in scholarly engagement within humanities and social sciences. Global contributions from 60 countries, led by the USA, showcase an international landscape, and English emerges as the predominant language. (Der) Islam-Zeitschrift für Geschichte und Kultur des Islamischen Orients and Journal of Archaeological Science Reports stand out as the most prolific journals across all fields, followed by Journal of Archaeological Science. This highlights the growing significance of archaeology in the research on early Islam. The top authors with the most publications N. Schibille, I. Taxel, and G. Bar-oz and most cited authors I. C. Freestone, J. Henderson, and Y. Avni shape the field. Financial support from organizations like the European Research Council (ERC), the Spanish Government and the Israel Science Foundation signals strategic investments in Islamic studies. Lastly, a keyword analysis emphasizes prevalent themes, such as Islam, early Islam, early Islamic period, and Qur’ān, providing a concise snapshot of the field’s contemporary focus. These insights underscore the rising international importance of Islamic research. Recognizing the limitations of the present study, this bibliometric analysis offers a foundational framework for future research by inspiring further scholarly exploration of emerging trends and thematic gaps in the field.